Perbedaan efek ekstrak buah naga merah (Hylocereus polyrhizus) dan ekstrak buah naga putih (Hylocereus undatus) terhadap kadar kolesterol total tikus putih (Rattus norvegicus) - Prakoso, Luthfi Octafyan; Yusmaini, Hany; Thadeus, Maria Selvester; Wiyono, Sugeng (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
This study aimed to compare the effect of red dragon fruit extract (Hylocereus polyrhizus) and white dragon fruit extract (Hylocereus undatus) to total cholesterol levels in white rats (Rattus norvegicus). Total of 30 males white wistar strains were divided into five treatments i.e: (1) standard feed and Na-CMC 1% (K1), (2) standard feed and quail egg 10ml/kgBW (K2), (3) standard feed, quail egg 10ml/kgBW and simvastatin dose 0,72mg/day (P1), (4) standard feed, quail egg 10ml/kgBW and red dragon fruit extract dose 60mg/200gBW/day (P2), (3) standard feed, quail egg 10 ml/kgBW and white dragon fruit extract dose 120mg/200gBW/day (P3). The intervention was carried out for 14 days after 7 days acclimatization period. Data was analyzed by One Way ANOVA test and continued with Post Hoc Bonferroni test (p=0.05). In P2 group, there was a difference of total blood cholesterol level by 25.83 mg/dl compared with the positive control group and statistically significant (p<0.05). In P1 and P3 group there were difference in cholesterol levels of 9.5 mg/dl and 11.5 mg/dl compared with the positive control group, but not statistically significant (p>0.05). The comparison between red dragon extract group and white dragon extract showed a non-significant difference (p>0.05). Red dragon fruit extract and white dragon extract have a potential effect to improve hypercholesterolemia conditions.